We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
339
1
avatar+10 

The explicit rule for a sequence is given. 

an=3(1/6)^n−1

 

Enter the recursive rule for the geometric sequence.

a1= ;  an=  

 Feb 28, 2019

Best Answer 

 #1
avatar+18961 
+2

a1=3  , an = an-1  * 1/6

 Feb 28, 2019
 #1
avatar+18961 
+2
Best Answer

a1=3  , an = an-1  * 1/6

ElectricPavlov Feb 28, 2019

3 Online Users